2003
DOI: 10.1038/nature01356
|View full text |Cite
|
Sign up to set email alerts
|

Constant elevation of southern Tibet over the past 15 million years

Abstract: The uplift of the Tibetan plateau, an area that is 2,000 km wide, to an altitude of about 5,000 m has been shown to modify global climate and to influence monsoon intensity. Mechanical and thermal models for homogeneous thickening of the lithosphere make specific predictions about uplift rates of the Tibetan plateau, but the precise history of the uplift of the plateau has yet to be confirmed by observations. Here we present well-preserved fossil leaf assemblages from the Namling basin, southern Tibet, dated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
410
2
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 584 publications
(438 citation statements)
references
References 21 publications
20
410
2
6
Order By: Relevance
“…One explanation for these changes is that at that time the surface of the plateau rose abruptly 1000 m or more [e.g., Harrison et al, 1992;Molnar et al, 1993], but much less than the full 5000 m present-day elevation of the plateau. Estimates of paleo-elevations of southern Tibet do not support, but rather contradict, this idea; essentially all such estimates show little change since 10 Ma to perhaps 25-35 Ma [Currie et al, 2005;DeCelles et al, 2007;Garzione et al, 2000aGarzione et al, , 2000bRowley and Currie, 2006;Rowley et al, 2001;Saylor et al, 2009;Spicer et al, 2003]. Because uncertainties in all arẽ 1000 m, however, let us consider the possibility that the average elevation of Tibet was 1000 m lower at 10-15 Ma than today.…”
Section: Discussion: Possible Relevance To Paleoclimatementioning
confidence: 85%
“…One explanation for these changes is that at that time the surface of the plateau rose abruptly 1000 m or more [e.g., Harrison et al, 1992;Molnar et al, 1993], but much less than the full 5000 m present-day elevation of the plateau. Estimates of paleo-elevations of southern Tibet do not support, but rather contradict, this idea; essentially all such estimates show little change since 10 Ma to perhaps 25-35 Ma [Currie et al, 2005;DeCelles et al, 2007;Garzione et al, 2000aGarzione et al, , 2000bRowley and Currie, 2006;Rowley et al, 2001;Saylor et al, 2009;Spicer et al, 2003]. Because uncertainties in all arẽ 1000 m, however, let us consider the possibility that the average elevation of Tibet was 1000 m lower at 10-15 Ma than today.…”
Section: Discussion: Possible Relevance To Paleoclimatementioning
confidence: 85%
“…Uplift of the plateau began approximately 40 million years ago (Mya) in the Eocene (Chung et al, 1998). Recent evidence indicates that the southern margin reached its present elevation approximately 15-22 Mya (Guo et al, 2002;Spicer et al, 2003) and that the whole plateau may have attained its present altitude by 7-8 Mya (Harrison et al, 1992). Orogeny along the eastern margin of the plateau since the early Miocene ($22 Mya) has created high mountains and deep valleys (Li et al, 1995), which are thought to have profoundly accelerated the diversification of plant species through local vicariance, secondary contact, and ecological speciation events (Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Yangbajing graben northwest of Lhasa [19], vegetation succession from forest to grassland in northern Pakistan [20] and enhanced upwelling current on the Arabian Sea coast [21] were all recognized as important evidence for the TP uplift during the late Miocene, and some scholars believed that the TP could have reached its full height around 8 Ma [19]. Afterwards some researchers speculated that the TP had basically reached its maximum height in the middle Miocene (14-15 Ma), and then changed little or even declined slightly according to research on the timing of Himalayan normal fault activity [22] and fossil leaves of paleoplants in southern Tibet [23]. Recently some scholars, based upon magnetic stratigraphy and sedimentology studies of basins in the central and northern TP [24] and the oxygen isotope data of basins in the central TP [25], recognized that the central TP could have reached its current height in the middle and late Eocene .…”
Section: Geological Recordsmentioning
confidence: 99%
“…Meanwhile, the eolian deposition also recorded the long-term process of aridification in inland Asia. The oldest eolian loess found in northern China appeared in the early Miocene (22)(23)(24)(25) [4,33,34], a critical period around which the environment transformed from a planetary circulation system into a monsoon-dominated pattern, as indicated by integrated studies of Asian paleoenvironmental records [35][36][37]. Both continental [38] and marine [39] eolian deposition records showed that aridification of inland Asia was significantly intensified during recent 3-4 Ma since the Pliocene.…”
Section: Geological Recordsmentioning
confidence: 99%